Perspektif Diskriminasi Gender Terhadap Penanganan Penyalahgunaan Narkoba Pada Perempuan - Rika, Antika Anta; Humaira, Fasha; Legistiana, Salsa; Puanandini, Dewi Asri (CV. Ulil Albab Corp, 2024)
The purpose of this study is to explain the suitability of applying a gender perspective if applied in the process of handling drug abuse in women so that women. The research was carried out using qualitative methods, using phenomenological methods, namely understanding or studying human life experiences based on the problems they experience. Data collection techniques were carried out through interviews, observation, and documentation. The results showed that the implementation of gender-responsive policies has absolutely been implemented and carried out both from rehabilitation procedures that are restorative in nature and legal procedures that provide justice to women victims of abusers, starting from the process of arrest, investigation, detention, and sentencing in accordance with regulations that are considered sensitive to women and a number of general rules that have been compiled previously.